PENYUSUNAN DAN PENGAPLIKASIAN MODEL DESA DIGITAL BERBASIS TATA KELOLA DI PEMERINTAH DESA TEGAL KECAMATAN KEMANG KABUPATEN BOGOR - Dina Fadiyah; Ayi Karyana; Daniel Pasaribu; Nong Ayu Triyanti Utami Hakim; Sapto Setyo Nugroho; Laras Ayu Andini (LPPM Universitas Islam Darul 'Ulum Lamongan, 2023)
This program focuses on designing a Governance-based Digital Village model. Digital Village is designed as a starting point for building social resilience, economic resilience and ecological/environmental resilience (Building Village Index). The difference between the design of this Digital Village and existing best practices is that this program makes media, websites and applications more as instruments, while the substance to be emphasized is on government literacy, especially in fulfilling digitalization on transparency, accountability and participation in Government and Village Communities.